The Role of the Village Head in Managing Bumdes Based on Law no. 06 of 2014 concerning Villages in Realizing Community Welfare Perspective of Islamic Law (Case Study of Bumdesa Aek Haruaya, Portibi District, North Padang Lawas District) - Roufdy Rizky Prasetyo; Khalid (Warmadewa Press, 2024)
This study uses a case study of BUMDes Aek Haruaya, Portibi District, Padang Lawas Utara Regency, to analyze the function of the Village Head in the management of Village-Owned Enterprises (BUMDes) based on Law No. 06 of 2014 on Villages and from an Islamic legal perspective. The primary goal of this study is to assess the Village Head's performance in managing BUMDes and the ways in which this management promotes the welfare of the village community. Field study using a descriptive qualitative technique is the research methodology employed. Through observations, interviews, and pertinent document analyses, data were gathered. According to the report, the Village Head is crucial to the planning, implementation, and evaluation of BUMDes programs. According to Law No. 06 of 2014, the Village Head is expected to manage BUMDes with high transparency and accountability. From an Islamic legal perspective, the management of BUMDes should adhere to principles of justice, welfare, and economic sustainability. The study also identified several challenges, including a lack of resources and training. The main recommendations include enhancing the Village Head's capacity through training, increasing resource allocation, and implementing effective monitoring and evaluation systems. The conclusion of this study emphasizes the importance of the Village Head's role in managing BUMDes to achieve community welfare, while adhering to legal regulations and Islamic principles.